Malay's perception of Islamic banking credibility - Huzaimah Huzaimah; Romli Romli; Maya Panorama (Universitas Negeri Surabaya, 2022)
This study aims to analyze the perceptions and preferences of the Malay community towards Islamic banking and examine the opportunities and challenges of Islamic banking in maintaining its credibility. This research method is carried out with a quantitative descriptive approach through a survey of 100 respondents. The sampling technique used was accidental sampling through the distribution of google forms. The study results indicate that the development of the number of customers of Islamic banks has indeed increased. However, compared to conventional banks, it still dominates the number of customers who save in conventional banks even though the Malay community, which is predominantly Muslim, should be the dominant interest in Islamic banks. There are various perceptions of the Malay community towards Islamic banking. Some Malay people think that Islamic banks are stated in a profit-sharing manner the same as conventional banks, with the term interest only differing in mentioning term. Due to the lack of promotion, many Malay people still use conventional banks for economic transactions. Human resources management influences the perception of the Malay community towards Islamic banking.